United Kingdom Survey of Culture-Negative Peritonitis and Dialysate Sampling Practice. Issue 1 (January 2016) - Odudu, Aghogho; Turner, Jake; Coomer, Kirstine; Salmon, Laura; Yazdani, Farah; Leung, Janson
Peritonitis is a major cause of technique failure in peritoneal dialysis (PD) and accurate diagnosis ensures successful management and avoids unnecessary antibiotic exposure. United Kingdom (UK) registry data on peritonitis rates are not routinely reported. We conducted an electronic survey amongst senior PD nurses and microbiologists to obtain information about PD effluent sampling and processing practices in the UK. The survey was completed by 53 of 79 centres (67% response rate). The median annual culture-negative rate was 15% (range 5 - 38%). The main findings were wide variation in reported sampling volumes and processing methods that may in part explain the variation in culture-negative rates. Adherence to guidelines might reduce culture-negative rates informed by reporting data into national registries.